Renal imaging in children with chronic kidney disease - Rahmawati, Wiwit; Muryawan, Heru; Prabowo, Farah (Paediatrica Indonesiana, 2013)
Background Chronic kidney failure is a cause of death in children. Diagnosing chronic kidney disease is often made by clinical manifestations, laboratory findings and ultrasonography or other imaging tests. Early detection of chronic kidney disease is needed for education and management of the disease. Objective To describe renal imaging findings and mortality in children with chronic kidney disease . Methods This was a cross-sectional study on children with kidney diseases who were inpatients at Dr. Kariadi Hospital from January 2008 to June 2011. Data were taken from medical records. Chronic kidney disease was confirmed by clinical manifestations, laboratory findings, and radiologic imaging. Renal ultrasound findings were determined by the radiologist responsible at that time. Results were presented as ft:equency distributions. Results Of 37 chronic kidney disease cases, 27 were males and 10 were females. Subjects' most common complaints were dyspnea (7 out of 3 7) and edema (30 out of 3 7) . Renal ultrasound imaging of subjects with chronic kidney disease yielded the following findings: reduced cortico-medullary differentiation (30 out of 3 7), bilateral echogenic kidneys (21 out of 3 7), reduced renal cortex thickness (4 out of 37) and small-sized kidneys (4 out of 37) . Eight of the 37 children died. These 8 subjects had the following radiologic imaging findin gs: both kidneys appeared small in size (4 out ofS), reduced 'renal cortex' thickness (4 out of 8), echogenic kidneys (6 out of 8), and reduced cortico-medullary differentiation (8 out of8). Conclusion Renal ultrasound imaging of pediatric subjects with chronic kidney disease revealed findings of reduced corticomedullary differentiation, bilateral echogenic kidneys, reduced renal cortex thickness, and small kidneys bilaterally.